ECO TOURISM: इको टूरिज्म - Bharadwaj, Anshu Arpan (International Journal of Research -GRANTHAALAYAH, 2015)
There is a correlation of tourist and environment. Currently, tourism is developing rapidly in all the countries of the world and it has taken the form of industry. The need for conservation of environment along with the development of tourism industry has worried the environmentalists of the world. Biodiversity and ecosystem are affected by uncontrolled tourism. Therefore, to control these side effects, tourists should be made aware about responsible tourism and eco-tourism. Responsible tourism prevents physical, social and cultural degradation. In responsive tourism, the tourism sector is developed in collaboration with the local community. Responsible tourists are the most caring and aware tourists from all sides. The performance of eco-tourism should also be increased for environmental protection. Tours in which a place is visited to see the natural scenery, fauna and flora and have fun related to any cultural aspect is called Eco Tourism. पर्यटक और पर्यावरण का सहसम्बन्ध है। वर्तमान समय में विश्व के समस्त देशों में पर्यटन का विकास तीव्रगति से हो रहा है और इसने उद्योग का रूप ले लिया है। पर्यटन उद्योग के विकास के साथ-साथ पर्यावरण के संरक्षण की आवश्यकता ने विश्व के पर्यावरणविदों को चिंतित कर रखा है। अनियंत्रित पर्यटन से जैव विविधता तथा पारिस्थितिकी तंत्र प्रभावित होता है। अतः इन दुष्परिणामों को नियंत्रित करने के लिए पर्यटकों को उत्तरदायी पर्यटन एवं इको टूरिज्म (पर्यावरणीय पर्यटन) हेतु जागरूक करना चाहिए। उत्तरदायी पर्यटन भौतिक, सामाजिक एवं सांस्कृतिक पतन को रोकता है। उत्तरदायी पर्यटन में स्थानीय समुदाय के सहयोग से पर्यटन क्षेत्र का विकास किया जाता है। उत्तरदायी पर्यटक सभी पक्षों का सर्वाधिक ध्यान रखने वाले और जागरूक पर्यटक होते हैं। पर्यावरण संरक्षण हेतु इको टूरिज्म का प्रद्यतन भी बढ़ाया जाना चाहिए। ऐसा पर्यटन जिनमें प्राकृतिक दृश्यों, जीव-जन्तुओं तथा वनस्पतियों को देखने और किसी सांस्कृतिक पहलू से जुड़े आनन्द लेने हेतु किसी स्थान की यात्रा की जाती है उसे इको टूरिज्म कहा जाता है।